2022
DOI: 10.1108/cdi-08-2021-0213
|View full text |Cite
|
Sign up to set email alerts
|

The social psychology of work engagement: state of the field

Abstract: PurposeResearch on work engagement is flourishing and shows important links between work engagement and career success. However, a systematic account of the social-psychological origins of engagement is largely lacking. In the paper, the author develops a theoretical model and discusses how employees actively influence and are influenced by employees' leader's, colleagues' and partner's work engagement.Design/methodology/approachThe author integrates literatures on emotional contagion, team work engagement, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 79 publications
3
59
1
4
Order By: Relevance
“…, 2020). Also, it would also be important to consider the impact of leadership style and team-level interventions targeted at increasing employee involvement in PWD (Bakker, 2022). Moreover, PWD can also be an antecedent of beneficial work outcomes (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2020). Also, it would also be important to consider the impact of leadership style and team-level interventions targeted at increasing employee involvement in PWD (Bakker, 2022). Moreover, PWD can also be an antecedent of beneficial work outcomes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may focus on how individual differences and job characteristics can predict employee involvement in PWD . Also, it would also be important to consider the impact of leadership style and team-level interventions targeted at increasing employee involvement in PWD (Bakker, 2022). Moreover, PWD can also be an antecedent of beneficial work outcomes (i.e.…”
Section: Playful Work Designmentioning
confidence: 99%
“…Examination of the research literature on work engagement (see, for example, Bakker, 2022) provided initial guidance for study of interventions that link to enhancement and/or reinforcement of employee work engagement. In addition, from articles that have received much attention, citation and discussion over the past few years such as Schaufeli et al (2008), Bakker and Demerouti (2017) and Bakker and van Wingerden (2021), information is found that aids in developing an understanding of the dynamics of work engagement.…”
Section: Methodsmentioning
confidence: 99%
“…Bakker (2022) suggests that work engagement has become so popular that it has taken over the central role of job satisfaction in the organizational psychology discipline as job satisfaction represents a positive but low activation of employee well-being while work engagement represents a positive and highly activated form of employee well-being. Knight et al (2017) report that the interest shown in work engagement is globally reflected as the body of empirical research on the subject is observed across a range of countries and organization types, and demonstrates broad participant characteristics.…”
Section: Examination Of Concepts Linkages and Relationshipsmentioning
confidence: 99%
“…Specifically, employees enter a positive motivational state (i.e. work engagement; Bakker, 2022) that allows them to invest additional energy in their tasks when relying on job resources provided by the organization (e.g. autonomy, feedback) (for meta-analysis, see Nielsen et al, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%